Contested Time. Migrants’ Temporal Practices and Agency in Institutional Reception and Grassroots Solidarity at the Canary Islands - Giliberti, Luca; Fravega, Enrico (Italian Sociological Review, 2024)
During the pandemic, due to the worsening of the already weak local economies of different Western African countries (Morocco, Western Sahara, Mauritania, Senegal), the impermeabilisation of the Ceuta/Melilla border and the consequent redefinition of the main migration routes, the Atlantic route towards the Canary Islands – which was relevant between the late 1990s and early 2000s – regained significance in undocumented migration towards Europe. The emergency management of this flow of people, which since 2020 has brought thousands of migrants to the shores of the Canary Islands, has continued for months and months, through improvised forms of reception in camps (Muelle de la verguenza) and empty hotels (due to the pandemic crisis), until the establishment of migrants’ emergency reception centres. Facing the often-inhuman conditions of these centres, as well as the situations of temporal injustice and the risk of deportation, many migrants refuse institutional relocation, leaving the reception system and dwelling in the streets. In this way, albeit in an ambivalent dimension, they break the frame on the public discourse concerning them as mere subjects in need of care and containment, regaining at least partial control of their time and opening up to a series of encounters with the emerging solidarity networks from below. This paper, based on an ethnographic fieldwork carried out, during 2022 and the beginning of 2023, on the island of Gran Canaria, means to explore the complex relation between temporality and migrants’ agency, with particular attention to forms of institutional reception and grassroots hospitality.